Nickel-Catalyzed Regioselective Thiolation of Anilides with Thiols - Kianmehr, Ebrahim; Doraghi, Fatemeh; Foroumadi, Alireza (Synthesis, 2022)
An efficient method for direct thiolation of anilides with thiols using NiCl2·6H2O as the catalyst is developed. Using this method, the desired products were successfully synthesized in moderate to good yields. Initial mechanistic studies suggest that this reaction proceeds through a radical pathway.
Keywords: C–S cross-coupling; thiolation; nickel catalyst; acetanilides; thiols